Heat transfer and fuel transport in the intake port of a spark ignition engine - Colechin, Michael John Farrelly (1996)
Surface-mounted heat flux sensors have been used in the intake port of a fuel injected, spark ignition engine to investigate heat transfer between the surface, the gas flows through the port, and fuel deposited in surface films. This investigation has been carried out with a single-cylinder engine on which the cylinder head is from a production four valve per cylinder engine with a bifurcated intake port. The objective has been to establish how engine operating conditions affect trends in surface heat transfer rates both with and without fuel deposition on the surfaces, and to relate these to the mechanisms involved in the transport of fuel into the engine. The effects on these mechanisms of injector type and fuel characteristics have also been studied.